Contextual Learning by Local Wisdom to Improve The Understanding of Simple Machine Concept - Triyani, Esti; Putra, Ngurah Made Dharma; Alimah, Siti (widiyanto, 2019)
This study aims to describe the application of contextual approaches learning (CTL) by local wisdom toward the understanding of students on the concepts of simple machine subject. The research method applied in this study was Mixed Methods with the sequential explanatory design. The first stage of the quantitative method was done to obtain data on the improvement of the understanding of concepts; the second stage of qualitative methods was to support the quantitative data. The sample taken for this study was the fifth-grade students of SDN 3 Troso, with some 30 students and the fifth-grade students of SDN 4 Troso, with some 32 students. The data collection techniques used in this study tested techniques in the form of multiple choice questions and non-test techniques consisting of interviews, and documentation. The results of the analysis of gain test on the understanding concept showed an increase in the experimental class which was categorized as moderate at 0.45, meanwhile, the control class was in the low category at 0.28.